2019
DOI: 10.1093/ofid/ofz073
|View full text |Cite
|
Sign up to set email alerts
|

Histoplasmosis, An Underdiagnosed Disease Affecting People Living With HIV/AIDS in Brazil: Results of a Multicenter Prospective Cohort Study Using Both Classical Mycology Tests and Histoplasma Urine Antigen Detection

Abstract: Background Histoplasmosis is highly endemic in the American continent. This condition is associated with a high mortality, particularly in people living with HIV/AIDS (PLWHA). Diagnosis of histoplasmosis is usually late in South America, as Histoplasma antigen detection is rarely available. Here we determined the prevalence, risk factors, and outcome of histoplasmosis in PLWHA in Brazilian hospitals. Methods This was a prospective cohort study… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
75
4
10

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 79 publications
(91 citation statements)
references
References 35 publications
2
75
4
10
Order By: Relevance
“…Brazil, histoplasmosis was identified in 21.6% of the patients. In this study, the overall mortality was 22.1% in 30 days, decreasing to 14.3% in patients with a Histoplasma antigen test diagnosis (Falci et al, 2019).…”
Section: Discussionmentioning
confidence: 50%
“…Brazil, histoplasmosis was identified in 21.6% of the patients. In this study, the overall mortality was 22.1% in 30 days, decreasing to 14.3% in patients with a Histoplasma antigen test diagnosis (Falci et al, 2019).…”
Section: Discussionmentioning
confidence: 50%
“…74 The second study was prospective and reported sensitivity of 56.4% (44 of 78) in culture-proven cases using the IMMY ASR. 75 Although there were 447 controls in that study, they did not report specificity. The authors suggested that the sensitivity may have been reduced because of treatment with antifungal medications for at least 7 days before testing in 39.7% (35 of the 74) of cases.…”
Section: Antigen Detectionmentioning
confidence: 86%
“…A Brazilian study reported 19.6% (8 of 41) of patients had detected antibodies against H. capsulatum. 75 Another Brazilian study reported testing Western blot using deglycosylated histoplasmin antigen with sensitivity of 90%, specificity of 90.9% and accuracy of 90.3%. 80…”
Section: Serologymentioning
confidence: 99%
“…On the other hand, histoplasmosis, an emergent systemic fungal infection in HIV patients in Brazil and other Latin American countries [9,10], has not yet been described in the context of Covid-19. Therefore, here we report the case of a Covid-19 patient who was later diagnosed with histoplasmosis in Southern Brazil.…”
Section: Introductionmentioning
confidence: 99%